Beauty of Black and White: Autofluorescence-aided Differentiation of Serpiginous Choroiditis from Tubercular Serpiginous-Like Choroiditis - Khatri, Anadi; Gurung, Shanti; Sitaula, Ranju Kharel; Singh, Sweta; Tran, Anh N.T.; Akhavanrezayat, Amir; Thng, Zheng Xian; You, Eunice; Bromeo, Albert John; Than, Ngoc T.T.; Kharel, Muna; Gupta, Ankur Sudhir; et al. (Nepalese Journal of Ophthalmology, 2024)
Introduction: FAF is non-invasive, and important adjunctive tool to evaluate the progression of lesions in patients with SC. FAF can even help distinguish probable etiology by specific pattern recognition. The current index study analyzed and reported the strength of specific patterns to be more representative of SC or TB SLC.Objective: To characterize fundus autofluorescence (FAF) images for differentiating serpiginous choroiditis (SC) from tubercular serpiginous-like choroiditis (TB SLC).Methodology: The index study is a retrospective comparative analysis of FAF images of 25 consecutive patients, 11 with TB SLC and 14 with SC. The diagnosis of SC was made based on the clinical appearance and FAF findings, while TB SLC was additionally considered in patients with positive laboratory investigations and/or radiological tests for tuberculosis (TB) exposure or infection and therapeuticresponse to anti-tubercular therapy. The characteristic features evaluated on FAF images were centrality, multifocality, and parapapillary involvement of the lesion with or without extension.Result: Twenty-five patients (13 males, 12 females) with a mean age of 46.2 (SD 10.08) years were enrolled in the study. SC lesions were more central (ρ=0.92) and confluent (ρ=0.774). Parapapillary involvement was found to be associated with SC (ρ=0.690), and with extensions of the lesions along the arcades or the macular region, the association increased (ρ=0.786). Multifocality with peripheral lesions was negatively associated with SC (ρ=- 0.831).Conclusion: Centrally involving lesions with confluency on FAF is strongly associated with SC. Parapapillary involvement alone is considered characteristic for SC, but the current study has demonstrated that extension of this lesion along the arcades or the macular region is even more characteristic for SC.